Implementation of Kirkpatrick Model in Boarding Training Evaluation at BBPVP Bandung - Ellina Rienovita; Aqsha Azelta Ragawaluya; Zainal Arifin (Inovasi Kurikulum, 2025)
Training as a competency improvement activity requires evaluation to determine the program's effectiveness. This research is to analyze the evaluation of boarding member-based training programs using the Kirkpatrick model at level I (reaction) and level II (learning). This research uses a quantitative approach with descriptive methods. Data collection techniques were carried out by meansprogram's effectiveness of observation, questionnaires, and documentation studies. The population was 192 participants who participated in stage I training at BBPVP Bandung, and the sample used was 32 boarding participants from the ICT vocational. Data analysis using descriptive quantitative in the form of percentages. This study's findings are the reaction level of boarding participants during training in the ICT vocational program at BBPVP Bandung in the “Good” category. However, some participants were dissatisfied with the services of the organizing committee, which were not responsive and solutive and provided inadequate facilities for less skilled instructors. Judging from the learning outcomes, participants experienced an increase, so participants were said to be competent and received certificates. There is a negative impact, namely the many rules that psychologically make some boarding participants feel unfree and burdened because they cannot adapt to their environment.   Abstrak Pelatihan sebagai kegiatan peningkatan kompetensi memerlukan evaluasi untuk mengetahui keefektifan program. Penelitian ini untuk menganalisis tentang evaluasi program pelatihan berbasis boarding member dengan menggunakan model Kirpatrick pada level I (reaction) dan level II (learning). Penelitian ini menggunakan pendekatan kuantitatif dengan metode deskriptif. Teknik pengumpulan data dilakukan dengan cara observasi, angket/kuesioner, dan studi dokumentasi. Populasi berjumlah 192 peserta yang mengikuti pelatihan tahap I di BBPVP Bandung dan sampel yang digunakan berjumlah 32 peserta boarding dari kejuruan TIK. Analisis data meggunakan deskriptif kuantitatif berupa persentase. Hasil temuan dalam penelitian ini adalah tingkat reaksi peserta boarding selama mengikuti pelatihan pada program kejuruan TIK di BBPVP Bandungdalam kategori “Baik”. Namun, sebagian peserta merasa kurang puas dengan pelayanan panitia penyelenggara yang tidak responsif dan solutif, fasilitas yang kurang memadai hingga instruktur yang kurang terampil. Dilihat dari hasil pembelajarannya, peserta mengalami peningkatan sehingga peserta dikatakan kompeten dan mendapatkan sertifikat. Terdapat dampak negatif yakni banyaknya peraturan sehingga secara psikologis membuat sebagian peserta boarding merasa tidak bebas dan terbebani karena tidak dapat beradaptasi dengan lingkungannya. Kata Kunci: boarding member; hasil belajar; model evaluasi Kirkpatrick; reaksi